Batch and Column Studies for the Removal of Lead(II) Ions from Aqueous Solution onto Lignite - Rifaqat Ali Khan Rao; Moonis Ali Khan; Fouzia Rehman (Adsorption Science & Technology)
The effectiveness of lignite for the removal of Pb(II) ions from aqueous solution has been evaluated. The maximum adsorption of Pb(II) ions onto lignite was 98%. The adsorption depends on the initial concentration of Pb(II) ions, the pH, the adsorbent dosage, the temperature and the contact time. Kinetic studies showed that the pseudo-second-order kinetic model provided the best fit to the experimental data. The adsorption process was found to be endothermic and spontaneous. The mean free energy values indicated that adsorption occurred via a chemisorption process. Both the Langmuir and Freundlich models provided good fits to the experimental data obtained at 40 °C, as indicated by the χ 2 -test. The breakthrough and exhaustive capacities were found to be 5 mg/g and 35 mg/g, respectively. The percentage recovery of adsorbed Pb(II) ions by column methods was ca. 80% when 0.1 M HCl was used as the eluent.